Drivers of Strategic Contestation in South America - Daniel Flemes; Leslie Wehner (German Institute of Global and Area Studies (GIGA), 2012)
The politics of contestation on the part of secondary regional powers such as Argentina, Chile, Colombia and Venezuela towards Brazil as the regional leader oscillate between competition and cooperation, inasmuch as the South American region has one regional power and is a zone of negative peace without aggressive rivalries. The secondary powers use different tactics, which constitute their respective foreign policy strategies, to soft balance Brazil. These tactics include alliance building, entangling diplomacy, binding, and omnienmeshment. This paper identifies, first, the specific drivers of contestation towards Brazil and, second, why the secondary powers' foreign policy strategies vary in how they directly or indirectly contest the rise of Brazil at the regional and international levels. The paper demonstrates that in a regional order such as that of South America, which is characterized by relative stability, domestic drivers of contestation are key to explaining secondary powers' varied strategic responses to the regional power.
Keywords: 300; secondary powers; regional powers; politics of contestation; foreign policy strategies; Brazil; Argentina; Colombia; Chile; Venezuela; Außenpolitik; Geopolitik; Internationale Beziehungen; Südamerika